Folate synthesis in higher-plant mitochondria: coupling between the dihydropterin pyrophosphokinase and the dihydropteroate synthase activities. - Mouillon, Jean-Marie (2002)
The plant enzyme 6-hydroxymethyl-7,8-dihydropterin pyrophosphokinase/7,8-dihydropteroate synthase (HPPK/DHPS) is a mitochondrial bifunctional protein involved in tetrahydrofolate synthesis. The first domain (HPPK) catalyses the pyrophosphorylation of 6-hydroxymethyl-7,8-dihydropterin (dihydropterin) by ATP, leading to 6-hydroxymethyl-7,8-dihydropterin pyrophosphate (dihydropterinPP(i)) and AMP. The second domain (DHPS) catalyses the next step, i.e. the condensation of p-aminobenzoic acid (p-ABA) with dihydropterinPP(i) to give 7,8-dihydropteroate (dihydropteroate) and PP(i). In the present article we studied the coupling between these two reactions. Kinetic data obtained for the HPPK domain are consistent with an ordered Bi Bi mechanism where ATP binds first and dihydropterinPP(i) is released last, as proposed previously for the monofunctional Escherichia coli enzyme. In the absence of p-ABA, AMP and dihydropterinPP(i) accumulate and negatively regulate the reaction. In the presence of p-ABA, the rates of AMP and dihydropteroate synthesis are similar, indicating a good coupling between the two reactions. DihydropterinPP(i), an intermediate of the two reactions, never accumulates in this situation. The high specific activity of DHPS relative to HPPK, rather than a preferential channelling of dihydropterinPP(i) between the two catalytic sites, could explain these kinetic data. The maximal velocity of the DHPS domain is limited by the availability of dihydropterinPP(i). It is strongly feedback-inhibited by dihydropteroate and also dihydrofolate and tetrahydrofolate monoglutamate, two intermediates synthesized downstream in the folate biosynthetic pathway. Thus the HPPK domain of this bifunctional protein is the limiting factor of the overall reaction, but the DHPS domain is a potential key regulatory point of the whole folate biosynthetic pathway.